Heparin-induced thrombocytopenia after MitraClip: A case report - Özge Çetinarslan; Ümit Yaşar Sinan; Emir Barış Ökçün; Cengiz Çeliker; Nuh Nazmi Gültekin (KARE Publishing, 2018)
Heparin-induced thrombocytopenia (HIT) and heparin-induced thrombocytopenia and thrombosis are potentially fatal adverse reactions to heparin therapy caused by the formation of polyclonal antibodies against the platelet factor 4-heparin complex. Fatal limb and organ damage or death may occur as a result of this immunological drug reaction. Described in this case report is the management of a patient who developed HIT after undergoing a MitraClip transcatheter mitral valve repair. The aim was to encourage clinicians to pay special attention to a frail patient who receives heparin therapy and to advise clinicians that clinical scores and laboratory tests should be used as a complement for certain diagnosis. The decision about continuation or cessation of heparin therapy is an important cornerstone for hospitalized patients with HIT.